ROLE OF EVENTFULNESS IN SOCIO-ECONOMIC DEVELOPMENT OF NEIGHBORHOODS (CASE STUDY: SHIRAZ, IRAN) - Aeizh AZMI; Khojasteh HASHEMI (European Journal of Geography)
Festivals have various economic and social impacts at the neighbourhood level, and this paper aimed to explore such impacts. The statistical population consisted of local experts, including the specialists, municipality authorities, and researchers of tourism and eventfulness. The total population sampling was performed as the qualitative research up to the saturation point. The findings showed that the eventfulness contributes to the economic and social development of the neighbourhoods, albeit periodically. Moreover, it was found to bring some benefits, including the job creation, increased ancillary income, and local economic interactions. The event organization process showed that the events have become governmentalized and religious. However, the results of the study indicated that the eventfulness has a significant effect on the increased social capital at the neighbourhood level, resulting in the increased public participation and quality of life.